Mechanical properties of molecularly thin lubricant layers: experimental methods and procedures - Becker, Thomas; Mugele, F. (IOP Publishing Ltd, 2005)
We present a new experimental set-up and experimental strategies designed for investigating dynamic processes in molecularly thin lubricant layers. The experimental set-up is an extension of a conventional surface forces apparatus, which allows for two-dimensional imaging of the thickness of liquid layers confined between two atomically smooth mica surfaces. We present details of amica surface preparation technique that eliminates otherwise frequently encountered contamination of the surfaces with nanoparticles, which were recently shown to affect surface forces measurements. Multiple-beam interferometry results in a thickness resolution of approximately 0.2 nm. The data analysis relies on fitting of numerically calculated optical transmission spectra of asymmetric multilayer Fabry–Perot interferometers. The lateral resolution and time resolution are determined by the optical resolution of the video microscopy and the frame rate of the digital CCD camera, respectively. Furthermore, we summarize several results and new insights into the collapse dynamics of thin lubricant layers that were obtained with this technique.